Etika Non-Kekerasan Jawdat Saʿīd dan Teks Hadis: Sebuah Kajian Pemikiran dan Relevansi Kontemporer - Ridho Wicaksono; Agung Danarta (MISYKAT Jurnal Ilmu-ilmu Al-Quran Hadist Syari ah dan Tarbiyah, 2025)
This article examines Jawdat Saīds concept of non-violence and its relevance to contemporary hadith studies. By analyzing key prophetic traditions, particularly those discouraging confrontation with enemies, emphasizing gentleness, elevating the value of knowledge, and highlighting social responsibility. Saʿīd develops an ethical hermeneutic that rejects offensive violence and positions the Sunnah as a foundation for peace. Unlike classical hadith scholarship centered on isnād–matn criticism, Saʿīd adopts a thematic and maqāṣid-oriented approach that prioritizes the preservation of life, justice, and education as core objectives of Islamic law. Through a close reading of his ideas, this study concludes that Saʿīd’s major contribution lies in shifting the orientation of hadith interpretation from literal legalism toward a humanistic social ethics relevant to contemporary political and social conflicts.